Evaluasi Karakter Agronomi Beberapa Genotipe Tetua Dan Hibrid Tanaman Kacang Panjang (Vigna sinensis L.) Berpolong Merah - Ardian Ardian; Genadi Aryawan; Y.C. Ginting (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Agronomic`s Characters Evaluation of Some Parental and Hybrid Genotypes of Red-Podded Yardlong Bean (Vigna sinensis L.) ABSTRACT. Yardlong bean is one of the legume plants that potential to be developed. Nowadays, many breeding activities had been conducted to develop yardlong bean, especially red-podded yardlong bean. The purpose of the study are (1) Evaluating the quality crop of some parental and hybrid genotypes of yardlong bean; (2) Getting the hybrid genotype that more superior from the parents (3) Estimating the variability value of yardlong bean genotypes from crosses of Pm x Lu, Lu x Pm, Pm x Cm, Cm x Pm, parental genotypes of Lu, Cm, and Pm. This study was conducted at Integrated Experimental Field of Agriculture Faculty, University of Lampung in March to June 2015. The used materials in this study are 7 genotypes of yardlong bean that consists of 3 parental and 4 hybrid genotypes. This study used completely randomized design with three replications. Further test used LSI (Least Significant Increase) test in α 0,05. Results indicated that: (1) Lu x Pm is the genotype that inherited by the characteristics of the parents, sweet taste from Lu and red-pod color from Pm; (2) Lu x Pm is the genotype that better than the parents because of having red-pod color, sweet-taste pod, and pod’s length that appropriate with consumer’s desire; (3) Genetic and phenotype variability of yardlong bean genotypes from crosses of Pm x Lu, Lu x Pm, Pm x Cm, Cm x Pm, parental genotypes of Lu, Cm, and Pm have narrow criteria for almost all characters except number of branch, °brix, and crispness level that have narrow criteria.